Kojic acid enhances the proliferation of human corneal epithelial cells via p38 and p21 signaling pathways. Issue 5 (September 2021) - Wei, Xi; Du, Lingling; Sun, Liyao; Wang, Chao; Song, Fanqian; Qian, Hua; Li, Xiaoguang; Guo, Xin; Tang, Xianling; Liu, Ping
Purpose: Treatment of corneal injury depends on the self-proliferation ability of human corneal epithelial cells (HCEp). Our previous study revealed kojic acid had the anti-senescence function on human corneal endothelial cells. In this study, we researched the enhancive proliferation effect of kojic acid in HCEp. Methods: Cell viability was evaluated by MTT assay. The expression of proliferation-related protein was detected by western blotting and immunofluorescence assay. Results: Kojic acid could enhance HCEp proliferation, characterized by promoting cell proliferation rate, decreasing the expression levels of p21, galectin 8 and ki67, and increasing that of p-p38. The p38 signaling pathway inhibitor, SB203580, could reverse the enhancive proliferation function of kojic acid. Furthermore, knockdown of p21 had similar enhancive proliferation effect to kojic acid. Conclusion: Kojic acid might enhance HCEp proliferation through p38 and p21 signaling pathways, potentially via reduced expression levels of galectin 8 and ki67. Hence, kojic acid might be a potential drug to accelerate the healing of corneal epithelial injury.